Subversive Drawing. Toni Hildebrandt on the Importance of Drawing from Joseph Beuys to Andy Warhol (KULT_online, 2018)
In times of all-encompassing digitalization, drawing with a pencil on paper seems to be a relict from a bygone world. Even as artistic practice it has become obsolete. Consequently, one could think, Toni Hildebrandt’s book Entwurf und Entgrenzung. Kontradispositive der Zeichnung 1955–1975 focuses on a chapter of art history lying more than forty years in the past. However, this study is not just a specialist contribution to a discussion led only by experts in the art movements in the 1960s and 70s. Alongside the deconstruction of the classical dispositif of drawing in the oeuvre of Hartung, Morris, Dieter Roth or Daniel Buren he points less at the historical than at the actual potential of drawing in our time.